2022
DOI: 10.1128/jmbe.00220-21
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reading Interventions on Student Understanding of and Misconceptions about Antibiotic Resistance

Abstract: Students possess informal, intuitive ways of reasoning about the world, including biological phenomena. Although useful in some cases, intuitive reasoning can also lead to the development of scientifically inaccurate ideas that conflict with central concepts taught in formal biology education settings, including evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…Many students reading the PubNavigator articles had mixed reasoning units and the inaccuracy of their statements primarily originated from misconceptions about a biological concept, rather than a misinterpretation of the reading or a problem with the article itself. Similar to other work, we identified several instances of both teleological and anthropocentric thinking in relation to the topics of evolution and natural selection in student discussions (Gregory, 2009; Pickett et al, 2022; Richard et al, 2017). Students often referred to evolution and natural selection as deterministic; traits evolved with direct goal of increasing the chances of survival and reproduction (i.e., teleological thinking).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Many students reading the PubNavigator articles had mixed reasoning units and the inaccuracy of their statements primarily originated from misconceptions about a biological concept, rather than a misinterpretation of the reading or a problem with the article itself. Similar to other work, we identified several instances of both teleological and anthropocentric thinking in relation to the topics of evolution and natural selection in student discussions (Gregory, 2009; Pickett et al, 2022; Richard et al, 2017). Students often referred to evolution and natural selection as deterministic; traits evolved with direct goal of increasing the chances of survival and reproduction (i.e., teleological thinking).…”
Section: Discussionsupporting
confidence: 80%
“…Students often disregarded individual variation and assumed that all inbred populations were absent of genetic diversity, that evolution was unachievable, and that all inbred populations would die over time. As these types of misconceptions are often associated with types of intuitive reasoning, it is unlikely that students would be able to resolve these misconceptions in an online discussion (Coley & Tanner, 2015, 2012; Pickett et al, 2022). Instead, instructors may choose to address these misconceptions in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a concluding activity, students should state whether given statements contain problematic phrasing within the specific context or not (single-choice with automatic feedback) and explain their decision (open-response). The design of the instruction on conditional metaconceptual knowledge was informed by previous research, models of self-regulated learning and metacognition, and educational proposals indicating that students need metacognitive conditional knowledge to know why and when to use their strategies and knowledge (e.g., their conceptions; see also Avargil et al, 2018), that explicitly addressing cognitive biases supports the development of conceptual knowledge (Pickett et al, 2022), that students' intuitive conceptions based on cognitive biases should and cannot be changed but rather that students should be enabled to become metaconceptually aware of and self-regulate them (Gonz alez Galli et al, 2020), and that the appropriateness of cognitive biases is context-dependent and students need to develop metacognitive knowledge about this context-dependency to draw on conceptions appropriate in a given context (Gresch, 2020; see also Sections 2.1 and 2.2).…”
Section: Intervention (B): Instruction On Conditional Metaconceptual ...mentioning
confidence: 99%
“…Helping students to overcome their misconceptions on ABR can be challenging as these misconceptions are widespread and deeply rooted. Pickett et al ( 16 ) and Hartelt and Minkley ( 17 ) found that giving students the correct, factual information on biological processes does not help them address their misconceptions, and observe that not much research has gone into how to address these challenges effectively. However, Wingert et al ( 18 ), Ginnobili et al ( 19 ), and Kampourakis ( 6 ) propose to use active learning that is designed to help students identify and destabilize their intuitive thinking, for instance through having students verbalize their reasoning and assess it for elements of teleological, essentialist, or anthropocentric argumentation.…”
Section: Introductionmentioning
confidence: 99%